PERAN UJI KOMPETENSI DALAM MENGUATKAN SOFT SKILL SISWA SMK AR-RAHMAN BEKASI UNTUK DAYA SAING INDUSTRI - Nurdin Effendi; Anis Lelitasari; Reza Ilyasa; Rifky Akbar Vetian; Gading Satria; Hoirul Anam (CV. Denasya Smart Publisher, 2025)
Competency testing (ujikom) is a crucial evaluation method in vocational education and training, assessing the extent to which students master knowledge and skills in a particular field. This Community Service Program (PkM) is dedicated to transferring knowledge and expertise from information technology lecturers and students to students of the Computer and Network Engineering (TKJ) program at SMK Ar-Rahman Bekasi. The implementation is carried out through a Softskill Competency Test (Ujikom) activity, specifically designed to strengthen students' non-technical abilities, which are highly demanded by the industry. The competencies tested include understanding operating systems and their installation, mastering computer software and hardware along with assembly, and a deep understanding of computer networks and their installation processes. Through the integration of enhanced soft skills with these technical competencies, it is expected that students will not only possess relevant expertise but also high mental readiness and adaptability, enabling them to effectively implement their knowledge in the workplace and daily life. This will significantly increase their competitiveness in the industry, ensuring that SMK Ar-Rahman Bekasi graduates are ready to face global challenges.